TERNAK SEHAT DENGAN PAKAN FERMENTASI DARI LIMBAH PERTANIAN SEBAGAI UPAYA KETAHANAN PANGAN - Tirmidzi, Farkhan Rama; Saltsabita Nourin Adelina; Agustin, Luly Alfiana; Envizha, Adiza Zhafrana; Baihaqi, Mohammad Alfan; Muhammad, Adibillah; Syafira, Rifda Nadia; Meisari, Intan; Septianingtyas, Tri Pangesti; Umniyyah, Zahratul; Yulianto, Roni; Khasanah, Nisaul (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
The role of Sidomukti Village as an agricultural and livestock center in Mayang District, Jember Regency creates obstacles, namely the lack of water when the dry season arrives, as a result of which farmers find it difficult to grow crops. This also has an impact on village farmers who use agricultural waste as animal feed. On the other hand, in the rainy season, the availability of agricultural waste as animal feed is very abundant, so it is necessary to utilize agricultural waste into alternative feed that has a longer shelf life through a fermentation process. The aim of empowering the community in Sidomukti Village through processing agricultural waste is to make fermented feed an alternative for breeders when the amount of feed is limited because of its long shelf life and increasing the appetite of livestock so that livestock become healthy. The partners of this program are breeders and farmers of Sidomukti Village through outreach and demonstration activities. The methods and stages carried out in this service activity include location observation, activity planning, outreach, practice/demonstration, and evaluation. There were 34 farmers as well as breeders and prospective breeders as participants in the socialization and demonstration. The fermented rice straw produced has a characteristic brownish color, a typical sour fermented aroma, and a slightly crumbly texture. Healthy livestock after providing fermented feed is one of the advantages of this program, namely not only as an alternative to the limited availability of animal feed, but also as an effort to maintain national food security.